Evaluation of psychiatric symptomatology, quality of life, and caregiver burden in mothers and children with primary immunodeficiency - Kilic, Nulufer; Kaya, Suheda; Tasci, Gulay; Ozsoy, Filiz; Kilic, Mehmet (Codon Publications, 2023)
Background: The present study aimed to evaluate the quality of life, depression, and anxiety scores of children with primary immunodeficiency (PID) and depression, anxiety scores, and the caregiving burden of their mothers. Methods: A total of 149 children aged 2-18 years and their mothers were included in the present study, along with 125 healthy children and their mothers as a control group. The Pediatric Quality of Life Inventory (PedsQL), Child Depression Inventory (CDI), and Screening for Child Anxiety-Related Emotional Disorders (SCARED) questionnaire were used based on the views of children and their mothers. The Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Temperament Evaluation of Memphis, Pisa, Paris, San Diego Autoquestionnaire (TEMPS-A), and Zarit Caregiver Burden Scale (ZCB) were used for the mothers. Results: According to children and their mothers, the scores of the PedsQL were lower than that of the control group (P < 0.05). In addition, according to the views of children and mothers, we found that PID children had higher depression and anxiety scores than healthy children (P < 0.05). The depression and anxiety levels of mothers in the patient group were also significantly higher than those in the control group (P = 0.05 and P = 0.001). Conclusion: Statistically, we found significantly lower psychosocial health summary scores and total scale score levels from the subclass of PedsQL in the patient group than in the control group. According to the views of both children and mothers, we observed that PID children had higher depression and anxiety scores than healthy children. It was also found that the BDI and BAI values in case of mothers in the patient group were significantly higher than those in the control group. (c) 2023 Codon Publications. Published by Codon Publications.
Keywords: anxiety; depression; primary immune deficiency; quality of life; temperament characteristics